Acute bilirubin encephalopathy and its associated risk factors in a tertiary care hospital, Pakistan - Ahmad, Munir (Pak J Med Sci, 2020)
OBJECTIVE: To determine the incidence of acute bilirubin encephalopathy (ABE) and its risk factors in neonates presenting with hyperbilirubinemia in a tertiary care children hospital. METHODS: This descriptive observational study was conducted from June 2018 to June 2019. A total of 300 infants who were admitted in neonatal ICU with diagnosis of hyperbilirubinemia in The Children’s Hospital & The Institute of Child Health, Multan, Pakistan were included in this period. Incidence of ABE was noted. ABE was divided into two categories on the basis of severity of symptoms; mild ABE and moderate to severe ABE. Total serum bilirubin (TSB) in all neonates was measured in all patients in hospital laboratory using colorimetric method. ABO incompatibility and Rh factor incompatibility was also noted for each neonate. RESULTS: Out of 300 neonates who presented with hyperbilirubinemia, ABE was diagnosed in only 42 (14.0%) neonates (mild ABE in 17 (5.7%) and moderate in 25 (8.3%). Out of 42 neonates of ABE, total serum bilirubin levels were 20-29.9 mg/dL in 24 (40.5%) neonates, and >30 mg/dL in 18 (42.8%) neonates. Pre-term birth was a significant risk factor of ABE; 23.8% in ABE and 10.70% in non-ABE (p-value 0.01). During treatment, 02 (4.76%) neonates expired due to ABE. CONCLUSION: In present study, ABE was diagnosed in 14.0% neonates who presented with hyperbilirubinemia. We found pre-term delivery as a significant risk factor of ABE.